An efficient green energy production by Li-doped Fe3O4 hydroelectric cell. (December 2020) - Gaur, Anurag; Kumar, Purushottam; Kumar, Anurag; Shah, Jyoti; Kotnala, R.K.
Abstract: In the present work, a hydroelectric cell (HEC) is fabricated to generate the electricity through the splitting of water into H3 O + and OH − ions without releasing any toxic by-product. Nanoporous Fe3 O4 and Li-doped Fe3 O4 materials have been synthesized by facile chemical co-precipitation method. BET (Brunauer–Emmett–Teller theory) results exhibited surface area of Li-doped Fe3 O4 to be 45 m 2 /g with pore radius ∼4 nm. The obtained powder was pressed into pellets of 4.08 cm 2 area. Then, Zn electrode was attached at one face of each pellet and silver on the opposite face to fabricate the hydroelectric cells. Cyclic Voltammetry (CV) curve of HEC demonstrates cathodic and anodic peak corresponding to a redox reaction at Zn and silver electrodes. The fabricated HEC of 4.08 cm 2 area of Li-doped Fe3 O4 delivers short circuit current, open-circuit voltage and off-load output power as 44.91 mA, 0.68 V, 30.80 mW, respectively. Ionic diffusion of the dissociated H3 O + and OH − ions have been confirmed by Nyquist curves of both HEC's compared to a dry state. The off-load 30.80 mW output power generation through Li-doped Fe3 O4 based Hydroelectric Cell of 4.08 cm 2 area is significant and has emerged as a viable alternative to other green energy sources. Graphical abstract: Image 1 Highlights: A hydroelectric cell (HEC) is fabricated to generate electricity through water splitting. Li-doped Fe3 O4 material shows 44.70 m 2 /g surface area with pore radius ∼4 nm. Interestingly, the output power generated by Li-doped Fe3 O4 HEC is 30.80 mW. The fabricated HEC may be an alternative to other green energy sources.